2012
DOI: 10.1155/2012/484591
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a “Rescue” Ciprofloxacin-Based Regimen for Eradication ofHelicobacter pyloriInfection after Treatment Failures

Abstract: The aim of our study was to evaluate the efficacy and tolerability of a ciprofloxacin-based regimen for H. pylori eradication failures as an alternative to bismuth based quadruple therapy. Methods. Design: prospective single-center study. Patients in whom a first eradication trial with omeprazole/esomeprazole, clarithromycin plus amoxicillin or tinidazole/metronidazole had failed were included. H. pylori status: established by histology, rapide urease test and polymerase chain reaction. Intervention: esomepraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Studies reporting duplicate data were excluded. After careful evaluation, 36 studies (including 3466 patients) were found to perform antibiotic susceptibility determinations and were included in the systematic review. Of these 36 articles, 24 reported cure rates according to antibiotic resistances/susceptibilities, including 37 arms of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reporting duplicate data were excluded. After careful evaluation, 36 studies (including 3466 patients) were found to perform antibiotic susceptibility determinations and were included in the systematic review. Of these 36 articles, 24 reported cure rates according to antibiotic resistances/susceptibilities, including 37 arms of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Among these patients, 2890 (83.4%) underwent endoscopy. In 16 of 36 articles, 19,23,24,[26][27][28][29]31,[34][35][36]39,[48][49][50] endoscopy was an inclusion criterion and was performed in all patients; therefore, the rate of acceptance of the procedure could not be evaluated. Nine additional articles performed endoscopy in all patients but did not state whether the procedure was an inclusion criteria or whether patients who rejected endoscopy had been excluded.…”
Section: Applicability Of Susceptibility Determination In Clinical mentioning
confidence: 99%
“…Interestingly, although the efficacy of CIP had been reported to underperform in acidic conditions and is currently discouraged by the Maastricht consensus report IV, 1 some studies have shown that the efficacy can be improved by having high dosage of PPI. 39,40 On the other hand, RFB combinations with newer alternative quinolones such as norfloxacin, levofloxacin, moxifloxacin and gatifloxacin have been frequently reported with successful rates >90% in recent years. The consistent success of PARC/PBRC therapy shown in this study suggests that it should be continued as the appropriate combination, at least in Australia and other countries with low quinolone resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Our mBCQT regimen featured twice-daily dosing, unlike previous studies. Dore et al[19] reported that daily two- or four-dose second-line regimens afforded similar eradication rates.…”
Section: Discussionmentioning
confidence: 99%